Pengaruh Ukuran Perusahaan, Struktur Aktiva, Dan Profitabilitas Terhadap Struktur Modal( StudiPadaPerusahaan sectormakananyang Terdapat di Bursa Efek Indonesia ( BEI ) Periode2012 - 2014 - Setyowati, Gesit; , Drs. Agus Endro Suwarno, M.Si (2016)
The purpose of this study was to investigate the influence of factors of company size, asset structure, ownership structure and the capital structure and know probability Which factors most influence on the company's capital structure at the food sector listed on the Stock Exchange the period 2012-2014. Quantitative methods used in reasert. Secondary data obtained from the company's financial statements sector Company food periode years 2012-2014 on the Stock Exchange of research Indonesia.The taken by purposive sampling in order to obtain a sample of 20 responden.Technique data analysis uses multiple linear regression analysis. Results obtained by t test variable firm size has no effect on the capital structure p signifikan value 0.328> 0.05; variable profitability has negative and significant effect on the capital structure with a p value 0.000 <0.05; variable asset structure has a significant influence on the capital structure with significant value 0.024 <0,05.Hasil coefficient of determination (R2) note that the adjusted R-square (R2) of 0.474, meaning variation variable capital structure changes can be explained by the variable size of the company, profitabilias and the structure of assets amounted to 47.4%. While the rest sebesar52,6% explained by other variables outside the model.